The Turan Army. Opportunities for a new military cooperation led by Turkey - Dávid Biró (Nuova Antologia Militare, 2021)
In the decades after the collapse of the Soviet Union, Turkish foreign policy took a new direction. During this period, new independent Turkic republics were established in the South Caucasus and Central Asia (Azerbaijan, Kazakhstan, Kyrgyzstan, Turkmenistan, and Uzbekistan). In the 2000s, we saw an increasingly active Turkish foreign policy towards these regions, which was multidimensional. One element of this was the development of strategic defense relations with these countries. One of the culminations of these relations in the future could be the creation of the “Turan Army”, a kind of military alliance of the Central Asians (gathering mainly Turkic countries). In October 2020, Turkish Defense Minister Hulusi Akar paid an official visit to several Central Asian countries, which revived the possibility of a new military alliance. The purpose of this study is to briefly outline the difficulties and opportunities, and attempts to illustrate Turkey’s regional leading role in creating a “Turan Army”.